Mekka in the Latter Part of the 19th Century by Christiaan Snouck Hurgronje: Historical Writing or Historical Sources? Mekka in the Latter Part of the 19th Century Karya Christiaan Snouck Hurgronje: Tulisan Sejarah atau Sumber Sejarah? - Nurhayati, Anifa; Haikal (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
The following paper aims to explore fundamental questions surrounding the status of the work of renowned orientalist Christiaan Snouck Hurgronje. Although the term